Effectiveness of Cognitive Behavioral Therapy on the Quality of Sleep in Women with Multiple Sclerosis: A Randomized Controlled Trial Study - Abbasi, Samira (Int J Community Based Nurs Midwifery, 2016)
BACKGROUND: Multiple sclerosis is accompanied by secondary clinical signs such as insomnia. Considering the side effects of drugs and also increasing acceptability of psychotherapy methods in health systems, we aimed to determine the effect of group cognitive behavioral therapy on the quality of sleep in women with multiple sclerosis in 2014. METHODS: This study is a randomized controlled clinical conducted on 72 women with multiple sclerosis who referred to medical centers of Isfahan. After convenience sampling, participants were randomly allocated into two equal groups of control (n=36) and intervention (n=36). In the intervention group, cognitive behavioral therapy was performed in 8 sessions. The control group, along with receiving the common drugs, participated in 3 group sessions and talked about their feelings and experiences. Data were gathered using Pittsburgh Sleep Quality Index (PSQI) and analyzed through independent t-test, Chi-square, Mann Whitney, ANOVA with repeated measure, using SPSS 18. RESULTS: There was a significant difference between the mean score of sleep quality of the control and intervention groups immediately and one month after the intervention (P<0.001). ANOVA with repeated measure test showed that the mean score of sleep quality of patients in the intervention group had a significant difference at three stages of before, immediately and one month after the intervention. CONCLUSIONS: According to the results of this study, cognitive behavioral therapy, as an effective and cost-effective therapy, could improve sleep quality in patients with multiple sclerosis. Trial Registration Number: IRCT2015012720833N1